Diagnostic accuracy of three clinical dehydration scales: a systematic review. Issue 4 (31st October 2017) - Falszewska, Anna; Szajewska, Hania; Dziechciarz, Piotr
Abstract : Objective: To systematically assess the diagnostic accuracy of the Clinical Dehydration Scale (CDS), the WHO Scale and the Gorelick Scale in identifying dehydration in children with acute gastroenteritis (AGE). Design: Three databases, two registers of clinical trials and the reference lists from identified articles were searched for diagnostic accuracy studies in children with AGE. The index tests were the CDS, WHO Scale and Gorelick Scale, and reference standard was the percentage loss of body weight. The main analysed outcomes were the sensitivity, specificity, positive likelihood ratio (LR) and negative LR. Results: Ten studies were included. In high-income countries, the CDS provided a moderate-to-large increase in the post-test probability of predicting moderate to severe (≥6%) dehydration (positive LR 3.9–11.79), but it was of limited value for ruling it out (negative LR 0.55–0.71). In low-income countries, the CDS showed limited value both for ruling in and ruling out moderate-to-severe dehydration. In both settings, the CDS showed poor diagnostic accuracy for ruling in or out no dehydration (<3%) or some dehydration (3%–6%). The WHO Scale showed no or limited value in assessing dehydration in children with diarrhoea. With one exception, the included studies did not confirm the diagnostic accuracy of the Gorelick Scale. Conclusion: Limited evidence suggests that the CDS can help in ruling in moderate-to-severe dehydration (≥6%) in high-income settings only. The WHO and Gorelick Scales are not helpful for assessing dehydration in children with AGE.